Competição intergenotípica entre feijoeiros (Phaseolus vulgaris L.) plantados em covas e em fileiras alternadas - Faria Vieira, Rogério (Revista Ceres, 2025)
This study involved three experiments. The following cultivars were used: Goiano Precoce (determinate growth habit, precocious), Ouro (indeterminate growth habit with erect branches), and Costa Rica (indeterminate growth habit with spreading branches).